Collaborative pairwise detection schemes for improving coverage in WSNs - Panayiotou, Christos G.; Michaelides, Michalis P. (My University, 2009)
One of the main applications of Wireless Sensor Networks (WSNs) is area monitoring (e.g., environmental monitoring). In such problems, it is desirable to maximize the area coverage which can be achieved by appropriately positioning the sensors (if possible) and/or by increasing the detection range of the sensors. This paper considers the latter. The emphasis is on pairs of closely spaced sensors that can collaborate in order to increase their collective area coverage. The main contribution of this work is to investigate collaborative detection schemes between a pair of sensor nodes and show that the area coverage achieved by each scheme depends on the distance between the two sensors. For closely spaced sensors, we propose the Enhanced Covariance Detector (ECD) that combines the energy and the covariance information from the two nodes by utilizing two different thresholds (one for the energy test statistic and another for the covariance).